Induction of a proinflammatory program in normal human thyrocytes by the RET/PTC1 oncogene - Borrello, Maria Grazia (National Academy of Sciences, 2005)
Rearrangements of the RET receptor tyrosine kinase gene generating RET/PTC oncogenes are specific to papillary thyroid carcinoma (PTC), the most frequent thyroid tumor. Here, we show that the RET/PTC1 oncogene, when exogenously expressed in primary normal human thyrocytes, induces the expression of a large set of genes involved in inflammation and tumor invasion, including those encoding chemokines (CCL2, CCL20, CXCL8, and CXCL12), chemokine receptors (CXCR4), cytokines (IL1B, CSF-1, GM-CSF, and G-CSF), matrix-degrading enzymes (metalloproteases and urokinase-type plasminogen activator and its receptor), and adhesion molecules (L-selectin). This effect is strictly dependent on the presence of the RET/PTC1 Tyr-451 (corresponding to RET Tyr-1062 multidocking site). Selected relevant genes (CCL20, CCL2, CXCL8, CXCR4, L-selectin, GM-CSF, IL1B, MMP9, UPA, and SPP1/OPN) were found up-regulated also in clinical samples of PTC, particularly those characterized by RET/PTC activation, local extrathyroid spread, and lymph node metastases, when compared with normal thyroid tissue or follicular thyroid carcinoma. These results, demonstrating that the RET/PTC1 oncogene activates a proinflammatory program, provide a direct link between a transforming human oncogene, inflammation, and malignant behavior.